2016
DOI: 10.2147/ijgm.s100237
|View full text |Cite
|
Sign up to set email alerts
|

Novel biomarker analysis of pleural effusion enhances differentiation of tuberculous from malignant pleural effusion

Abstract: Lymphocytic pleurisy is commonly observed in tuberculosis and cancer. Noninvasive biomarkers are needed to distinguish tuberculous pleural effusion (TPE) from malignant pleural effusion (MPE) because current clinical diagnostic procedures are often invasive. We identified immune response biomarkers that can discriminate between TPE and MPE. Fourteen pleural effusion biomarkers were compared in 22 MPE patients and five TPE patients. Of the innate immunity biomarkers, the median levels of interleukin (IL)-1β and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Many studies have reported the level of CXCL10 to be higher in human MPE, which is in line with our result that CXCL10 was higher in human MPE than in corresponding blood (data not shown). Taken together, these findings indicated that CXCL10 may be involved in the immune response to pleural disease . Accordingly, we focused the experiments in this study on CXCL10.…”
Section: Discussionmentioning
confidence: 93%
“…Many studies have reported the level of CXCL10 to be higher in human MPE, which is in line with our result that CXCL10 was higher in human MPE than in corresponding blood (data not shown). Taken together, these findings indicated that CXCL10 may be involved in the immune response to pleural disease . Accordingly, we focused the experiments in this study on CXCL10.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, IL-4 is one of the most detected cytokines in TB PE, and thus making probably the responsible signal to induce DC-SIGN expression in cells at this site ( 43 ). IL-13 is another cytokine that is present in the pleural cavity of active TB patients ( 44 ), and that is probably responsible for the mediating DC-SIGN expression in macrophages since its signaling pathway is considered to be equivalent to that of IL-4 ( 22 ). At the pulmonary tissue level, while we detected DC-SIGN-expressing cells with a morphology typical of dendritic cells and lymphocytes (likely B cells), there were also numerous DC-SIGN-expressing cells which also co-express the macrophage marker CD68 and CD163.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the average performance of IP-10, in accordance with Dheda’s results, we presented a considerable number of false positives (5 malignancies, 1 endometriosis, 1 cardiac failure and 1 hepatic failure). In a study published in 2016, TB and malignant pleural effusions were compared using several biomarkers, including IFN-γ and IP-10 [ 34 ]. In their sample of 27 patients (5 pleural TB and 22 malignant pleural effusion), IP-10 presented the best AUC when compared to IFN-γ (AUC 0.950 and cut-off 4,005 pg/mL vs AUC 0.830 and 100.5 pg/mL), with both presenting the same sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%